On the notion of international civil service: theoretical approaches and legal regulation - Seitimova Venera Н. (Journal of the Belarusian State University. Law, 2019)
The article deals with the definitions of «international civil service», «international civil servant», basic characteristics of the notions are analyzed. The author tracks the peculiarities of theoretical approaches and gives examples of different terms used as regards to the personnel of the international organizations in international and national legal acts. As the result of the given research the author suggests definitions of the notions «international civil service», «international civil servant», points at the preferential usage of the relevant terms depending on the issues and persons concerned.